Paracoccidioidomycosis in animals and humans - Bosco, Sandra De Moraes Gimenes [UNESP]; Bagagli, Eduardo [UNESP] (Springer Nature, 2018)
Paracoccidioidomycosis (PCM) is the most important systemic mycosis in Latin American countries, especially in Brazil, Colombia, Venezuela, and Argentina. The disease is caused by Paracoccidioides brasiliensis and P. lutzii, which are dimorphic fungi belonging to the Ajellomycetaceae. The disease is relatively common in humans, but poorly known in animals. The finding that nine-banded armadillos (Dasypus novemcinctus) are naturally infected by P. brasiliensis, systematically recovered from their tissues, has opened up new opportunities to better comprehend the fungus' eco-epidemiology. Armadillos are ancient South American mammals belonging to the order Xenarthra, which also comprises anteaters and sloths. The fungus was detected by nested PCR and histopathology in the anteater Myrmecophaga tridactyla and in the two-toed sloth Choloepus didactylus, respectively. The pathogen was also detected by molecular assays in different species of wild road-killed animals originating from PCM-endemic areas. In domestic animals, asymptomatic PCM infection has been detected by intradermal tests and serological surveys, e.g., in dogs, cats, sheep, horses, cattle, pigs, and chickens. Naturally acquired PCM disease was reported in three dogs with generalized lymphadenomegaly and hepatosplenomegaly. Certainly, PCM has been underdiagnosed in animals. Veterinarians should always keep this fungal infection in mind when dealing with animals from regions endemic/ enzootic for PCM.